Creación de dos Circuitos Turísticos Sustentables para el Desarrollo, Promoción y Fortalecimiento de la Actividad Turística en la Provincia de Los Ríos - Nicola Chong, Margareth Gabriela (2013)
The purpose of this project is to provide national and international tourism potential offered by the Province of Los Ríos and in this way to encourage tourists to visit this area of Ecuador, offering many natural, cultural and gastronomic. The main idea is to encourage people to have a new lifestyle through tourism, as it will lead to the improvement of their economic and social situation, providing a positive image of the province as another tourist place to visit. Permitted to provide a new source of income for this activity, thus further expanding tourism products while growing differents establishments offering quality tourism services, customized to meet the needs and requirements of visitors.